Deep-sea ascidians (Chordata, Tunicata) from the SW Atlantic: species richness with descriptions of two new species - Maggioni, Tamara; Taverna, Anabela; Reyna, Paola B.; Alurralde, Gastón; Rimondino, Clara; Tatián, Marcos (Zootaxa, 2018)
The understudied deep-sea benthic communities from the Southwestern Atlantic continental slope (200 m–3000 m depth) were sampled on August 2012 in an area located around 38°S that included the Mar del Plata submarine canyon. In these samplings we found a total of 16 ascidian species from six different families, of which two corresponded to new species. These were: Aplidium meridianum (Sluiter, 1906); Aplidium variabile (Herdman, 1886); Aplidium marplatensis Maggioni & Tatián (sp. nov. present work); Aplidium solitarium Maggioni & Tatián (sp. nov. present work); Synoicum georgianum Sluiter, 1932; Synoicum molle (Herdman, 1886); Synoicum sp.; Polysyncraton trivolutum (Millar, 1960); Sycozoa umbellata (Michaelsen, 1898); Ascidia meridionalis Herdman, 1880; Cnemidocarpa drygalskii (Hartmeyer, 1911); Styela squamosa Herdman, 1881; Pyura pilosa Monniot C. & Monniot F., 1974; Molgula pyriformis Herdman, 1881; Molgula setigera Ärnbäck-Christie-Linde, 1938 and Asajirus indicus (Oka, 1913). Based on morphological evidence, we propose the new synonymy: Molgula setigera Ärnbäck-Christie-Linde, 1938 = Molgula marioni Millar, 1960 = Molgula robini Monniot C. & Monniot F., 1983. We also propose to maintain Molgula pyriformis and Molgula malvinensis as separate species. We report: the extension of the distribution range of Aplidium meridianum, Synoicum georgianum, Polysyncraton trivolutum, Sycozoa umbellata, Cnemidocarpa drygalskii, Pyura pilosa and Molgula setigera, being the first time they are collected off La Plata River; the deepest registers for Synoicum georgianum, Poylsyncraton trivolutum, Sycozoa umbellata, Ascidia meridionalis, Pyura pilosa, Molgula pyriformis and Molgula setigera; and the shallowest register for Synoicum molle.